The value of control versus the value of time: A field experiment in Rwanda - Hickman, William; Kramer, Berber; Mollerstrom, Johanna; Seymour, Greg (International Food Policy Research Institute, 2023)
Agricultural development programs often aim to empower women by enhancing their control over income via new work opportunities, but as an unintended negative consequence, these programs can sometimes increase women's already heavy workloads. This raises the question of whether women themselves consider the increased control over income to be worth the additional work. To answer this, we need to know how much they value control over income and how much they value efforts to free up their time.